Social Construct of Business Entity's Performance Measurer: A Case Study of SME in Kudus - SITI MUTMAINAH; TRI JATMIKO WAHYU PRABOWO; SURYA RAHARJA (The Indonesian Journal of Accounting Research, 2013)
This research aims to study the performance measurement systems (PMS) practices in small and medium enterprises (SMEs). This qualitative research employs a case study methodology which investigates how the social construction on performance measurement system in Mubarokfood, an SME using society cultural sphere in Kudus. This study argues that ontologically PMS practice is a socially constructed reality. PMS, in the sense of such a reality, is seen as a collaborative process involving local culture, society and powerful actors. By using Mubarokfood as a research setting, it can be concludedthat the SME is committed to PMS because such practice is important for the company to gain legitimacy and maintain social harmony. Weber's concept on disenchantment of the world was irrelevant in the case of Mubarokfood. Mubarokfood is running on rationalization which develops new pattern in its spiritual aura, i.e., doing spiritual rationalization. Consequently there is no disconnection between spiritual and rational world